The Structure‐Function Relationship of Human Bleomycin Hydrolase: Mutation of a Cysteine Protease into a Serine Protease. (5th May 2022) - Zheng, Yi‐Zhen; Cui, Jingxuan; Wang, Yung‐Lin; Huang, Szu‐Jo; Lin, En‐Chi; Huang, Sheng‐Cih; Rudolf, Jeffrey D.; Yan, Xiaohui; Chang, Chin‐Yuan
Abstract: Human bleomycin hydrolase (hBH) catalyzes deamidation of the anticancer drug bleomycins (BLM). This enzyme is involved in BLM detoxification and drug resistance. Herein, we report the putative BLM‐binding site and catalytic mechanism of hBH. The crystal structures and biochemical studies suggest that hBH cleaves its C‐terminal residue without significant preference for the type of amino acid, and therefore can accordingly accommodate the β‐aminoalanine amide moiety of BLM for deamidation. Interestingly, hBH is capable of switching from a cysteine protease to a serine protease that is unable to cleave the secondary amide of hBH C‐terminus but reacts with the primary amide of BLMs. Abstract : Human bleomycin hydrolase (hBH) switches from a cysteine protease to a serine protease that selectively reacts with the primary amide of bleomycins (BLMs) but is unable to cleave the secondary amide of hBH C‐terminus.